Analisis Naratif Kebijakan: Kebijakan Ganja Medis di Indonesia - Widi Asmoro; Palupi Lindiasari Samputra (Research and Development Agency Ministry of Home Affairs, 2021)
Policy concern on medical marijuana utilization as diseases treatment or pain reliever still debated in many countries, also in Indonesia. This study aim to find government’s narrative relate to medical marijuana policy in Indonesia, analyze the resistance of its implementation, and formulate alternative strategies. Narrative Policy Analysis (NPA) applied to analyze the narrative disparity on government’s medical marijuana policies and to specify narrative form, as well as level of analysis, setting, character, plot, and moral of the policy narrative. Data gathered from trusted online documents such as public data, media coverage, or speech transcripts relevant to research issues from January 2019 to December 2020. Study find that 1) Government still forbid medical marijuana use in order to protect people from risk and unexpected problems; 2) Narrative policy develop by the government hampered by different belief system about marijuana and the lack of empirical study about medical marijuana in Indonesia; 3) Some of strategy recommendations to enhance government policy narrative related to medical marijuana were organize an open discussion with the contra community, conduct empirical study with academics to strengthen arguments and policy narrative, and socialize medical marijuana policy to various stakeholders.